Chemical synthesis of a reported p47phox/p22phox inhibitor and characterization of its instability and irreproducible activity - Zang, Jie; Cambet, Yves; Jaquet, Vincent; Bach, Anders (Frontiers in Pharmacology, 2023)
The NADPH oxidase 2 (NOX2) multi-subunit complex is a highly abundant and central source of reactive oxygen species. NOX2 is a key enzyme of the innate immune system involved in antibacterial response, but excessive NOX2 activity is involved in oxidative stress and inflammation in many diseases. Inhibition of NOX2 has great potential as a therapeutic strategy. An intriguing pharmacological approach for inhibiting NOX2 is to target the p47phox subunit and thereby block the protein-protein interaction with p22phox, whereby assembling and activation of NOX2 is prevented. However, the shallow binding pocket of p47phox makes it difficult to develop drug-like p47phox/p22phox inhibitors. Recently, the small molecule LMH001 was reported to inhibit the p47phox/p22phox interaction, reduce endothelial NOX2 activity, and protect mice from angiotensin II-induced vascular oxidative stress. These noteworthy results could have significant impact on the field of NOX2 pharmacology, as specific and efficient inhibitors are scarce. Here, we synthesized and tested LMH001 to have it available as a positive control. We established a robust synthetic route for providing LMH001, but subsequently we experienced that LMH001 is chemically unstable in aqueous buffer. In addition, neither LMH001 nor its breakdown products were able to inhibit the p47phox/p22phox interaction in a non-cellular fluorescence polarization assay. However, LHM001 was a weak inhibitor of NOX2 in a functional cell assay, but with same low potency as one of its breakdown products. These findings question the activity and suggested mechanism of LMH001 and constitute important information for other researchers interested in chemical probes for studying NOX2 biology.